O diário como expressão lírica em Cyro dos Anjos - Souza, Helane Santos (2016)
This dissertation objective is to make an analysis of how the genre diary is used in the Cyro dos Anjos’ novels: O amanuense Belmiro, Abdias and Montanha. Having such a priority we will seek to understand how this genre, for being fragmented and libertarian, enables a favorable environment for the exhibition of the personhood of the narrators. In this perspective, we will analyze the novels under the concept of diary, highlighting the peculiarities of this genre and analyzing how this structure contributes for the works in research. Therefore, we will use the theory of Philippe Lejeune (2008) about the diaristic format, as well as we will search for subsidies in the critical fortune of the literary works. Above all, we will rely on the readings of the novels, with the help of theories that have some connection with the proposed subject. Finally, we will show that the diary is the lyrical base of the three novels, as well as the connection point among them.